2017
DOI: 10.1002/jcu.22493
|View full text |Cite
|
Sign up to set email alerts
|

Massive pleural effusion on the contralateral side of a venous peripherally inserted central catheter

Abstract: A preterm newborn infant, delivered at 30 weeks of gestation and 965 g birth weight, developed respiratory distress with resistant hypoxia after a central catheter line was inserted via the right venae brachialis on postnatal day 21. Left-sided massive pleural effusion, collapsed left lung with air bronchograms, and bidirectional shunting through reopened ductus arteriosus were detected by targeted neonatal echocardiography. Hydrothorax was drained under sonographic guidance, producing a milky-white fluid bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
1
6
0
7
Order By: Relevance
“…In reports of ECC-related PE, most catheters were inserted from an upper extremity vein ( 1 4 , 6 , 13 , 15 ) but few were inserted from a lower extremity vein. Kua et al reported a case of ECC-related PE, in which the catheter was inserted from a lower extremity vein and located in the right iliac vein before migration to one of the tributaries of the azygous vein ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In reports of ECC-related PE, most catheters were inserted from an upper extremity vein ( 1 4 , 6 , 13 , 15 ) but few were inserted from a lower extremity vein. Kua et al reported a case of ECC-related PE, in which the catheter was inserted from a lower extremity vein and located in the right iliac vein before migration to one of the tributaries of the azygous vein ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…During removal, we noted that the catheter’s length was the same as after insertion, suggesting that it had been misplaced at the time of insertion itself. A similar case of misplacement during insertion has been reported previously also 1. So, to avoid this complication, some authors suggest using real-time ultrasound-guided PICC line insertion by experienced neonatologists as it is shown to decrease the catheter insertion duration as well as fewer manipulations when compared with the conventional technique 5…”
Section: Discussionmentioning
confidence: 58%
“…It was reported that PICC line can cause perforation of vascular structures to reach cavities (pleural, peritoneal and pericardial ones), which happened in our case 1. Studies have shown that limb movement, neck position and forceful flushing while insertion may change the position of the tip of the PICC line 7.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations